Next‐generation sequencing for the diagnosis of MYH9‐RD: Predicting pathogenic variants. Issue 1 (15th October 2019) - Bury, Loredana; Megy, Karyn; Stephens, Jonathan C.; Grassi, Luigi; Greene, Daniel; Gleadall, Nick; Althaus, Karina; Allsup, David; Bariana, Tadbir K.; Bonduel, Mariana; Butta, Nora V.; Collins, Peter; et al.
Abstract: The heterogeneous manifestations of MYH9 ‐related disorder (MYH9‐RD), characterized by macrothrombocytopenia, Döhle‐like inclusion bodies in leukocytes, bleeding of variable severity with, in some cases, ear, eye, kidney, and liver involvement, make the diagnosis for these patients still challenging in clinical practice. We collected phenotypic data and analyzed the genetic variants in more than 3, 000 patients with a bleeding or platelet disorder. Patients were enrolled in the BRIDGE‐BPD and ThromboGenomics Projects and their samples processed by high throughput sequencing (HTS). We identified 50 patients with a rare variant in MYH9 . All patients had macrothrombocytes and all except two had thrombocytopenia. Some degree of bleeding diathesis was reported in 41 of the 50 patients. Eleven patients presented hearing impairment, three renal failure and two elevated liver enzymes. Among the 28 rare variants identified in MYH9, 12 were novel. HTS was instrumental in diagnosing 23 patients (46%). Our results confirm the clinical heterogeneity of MYH9 ‐RD and show that, in the presence of an unclassified platelet disorder with macrothrombocytes, MYH9 ‐RD should always be considered. A HTS‐based strategy is a reliable method to reach a conclusive diagnosis of MYH9 ‐RD in clinical practice. Abstract : MYH9 ‐related disorder diagnosis is still challenging in clinical practice. We analyzed the genetic variants in more than 3, 000 patients with a bleeding or platelet disorder and identified 50 patients with a rare variant in MYH9 . In the presence of an unclassified platelet disorder with macrothrombocytes, MYH9 ‐RD should always be considered.